Pelatihan Perancangan Poster Pendidikan Menggunakan Dummy Tempel Pada Guru-Guru SDN 39 Cakranegara - Nurul Kemala Dewi; Siti Istiningsih; Mega Puspita Sari (Jurnal TUNAS, 2023)
According to the findings of field observations, the ability of teachers in class IV of SDN 39 Cakranegara to design posters is still insufficient. Teachers do not grasp how to create visually appealing posters. Observing posters in student books without practising them is the only way to learn to make posters. Poster design instruction has also never been provided. This issue must be addressed as soon as possible, and one way to do so is through this project. This projects aims to provide information on how to create effective educational posters. This activity was carried out through mentorship approaches such as (1) presentation from expert and (2) training workshops and practices in producing educational posters using sticky dummy. By the end of the activity, participants are expected to gain a wide understanding of educational posters as well as the skills to design effective posters.